AGRICULTURE OF KARALPAKSTAN IN CONDITIONS OF THE MANAGEMENT OF PLANNED DISTRIBUTING SYSTEM IN 1960-1980 YEARS - Abdukarimov, A.A. (SCIENCE and SOCIETY, 2020)
The article discusses the condition of 1960-1980s agriculture of Karakalpakstan, planned distributing system and its consequences, increasing in irrigated land under the cotton, bioclimatic measurements and ecological conditions becoming as a result of agrarian reforms.
Keywords: party leadership; artificial irrigation; social sphere; chemicalization cotton; agricultural policy; raw cotton; collector; cotton ginning industry; monoculture; bioclimat; ecological; pesticides; defoliation